Rancang Bangun Sistem Penjualan Tunai dan Penerimaan Kas Berbasis Multiuser - Rini Rubhiyanti; Sekar Putri Pertiwi; Febryantahanuji Febryantahanuji (STEKOM PRESS, 2020)
Sales are the main activity to generate profits. Sales and recording procedures that are good and according to company needs can be carried out with a sales accounting system. Cash sales and cash receipts are very important in an agency, because cash is an important asset. In recording sales and cash receipts, this agency still uses manuals. This study designed a system that is able to assist companies in calculating sales and cash receipts. With this cash sales and cash receipt information system, it is hoped that the procurement, sales planning and supervision will be carried out very well. besides that, it can also produce reports that are precise, accurate and efficient.